2016
DOI: 10.3390/ijerph13121217
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of Greenspace on Thermal Comfort in a Residential Quarter of Beijing, China

Abstract: With the process of urbanization, a large number of residential quarters, which is the main dwelling form in the urban area of Beijing, have been developed in last three decades to accommodate the rising population. In the context of intensification of urban heat island (UHI), the potential degradation of the thermal environment of residential quarters can give rise to a variety of problems affecting inhabitants’ health. This paper reports the results of a numerical study of the thermal conditions of a residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…Besides controlling the city's total number of green spaces through urban planning, other indicators should be introduced. Numerous studies in different countries have shown that the association of vegetation coverage and impervious surface parameters might be more closely related to thermal indicators than landscape area [39][40][41][42][43][44]. This study showed that the conversion between Green and Grey landscapes might not occur in the same intensity per unit area, resulting in a mismatch of LST increase and decrease.…”
Section: Spatial Imbalance Of Land Surface Temperature Change and Thementioning
confidence: 69%
“…Besides controlling the city's total number of green spaces through urban planning, other indicators should be introduced. Numerous studies in different countries have shown that the association of vegetation coverage and impervious surface parameters might be more closely related to thermal indicators than landscape area [39][40][41][42][43][44]. This study showed that the conversion between Green and Grey landscapes might not occur in the same intensity per unit area, resulting in a mismatch of LST increase and decrease.…”
Section: Spatial Imbalance Of Land Surface Temperature Change and Thementioning
confidence: 69%
“…Fourth, the UTCI (universal thermal climatic index), an index of the predicted body heat, was used to analyze comfort for the thermal environment [45,46]. It is expected that overall environments of myeong-dang sites according to feng shui thoughts could be scientifically analyzed through the above methods and that meaningful quantitative characteristics of its topographical types could be examined using comparative analyses [47,48].…”
Section: Evaluation Targets and Methodsmentioning
confidence: 99%
“…where feng shui is approached in terms of geography [10,48]. On the contrary, it may not be possible to consider environmental conditions separately from the geographical aspect if the research is conducted in terms of an environmental aspect, as presented previously in Chang's article [28].…”
Section: Topographic Analyses For Target Sitesmentioning
confidence: 99%
“…In a sense, carbohydrate-rich foods can be a way of self-medicating anti stress and the positive effect of carbohydrates on mood is proportional to the glycemic index of foods. For this reason they could represent the best allies to ght quarantine-related low mood thus giving rise to the so called 'emotional eating' [9][10][11]. This condition is further exacerbated by the disruption in everyday life that along with continuously hearing or reading about the pandemic, could have led to a stressful condition pushing people toward overeating and increasing the risk of developing obesity.…”
Section: Introductionmentioning
confidence: 99%